2017
DOI: 10.1111/his.13394
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations of neuroendocrine tumours of the lung

Abstract: deletions), but restriction of multiple endocrine neoplasia type 1 (MEN1) mutations to carcinoids. Highgrade carcinomas are also characterised by TP53 and RB1 gene inactivation. In this review, a critical analysis of the diagnostic and prognostic role of Ki67 labelling index and a concise discussion of the most relevant findings regarding molecular characterisation of lung neuroendocrine neoplasms are reported. In addition, we illustrate how the development of promising therapeutic strategies based on the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…The collective molecular data support this existing histological classification, with carcinoids and carcinomas displaying distinct mutational burdens and profiles (Swarts et al 2012, Simbolo et al 2017. For example, somatic TP53 mutations and loss of 3p are common in NE carcinomas, yet rare in carcinoids (Rossi et al 2018). These molecular differences are directly related to differences in tobacco exposure, which is known to cause TP53 and other mutations (Gibbons et al 2014).…”
Section: Lung Neuroendocrine Tumorssupporting
confidence: 67%
“…The collective molecular data support this existing histological classification, with carcinoids and carcinomas displaying distinct mutational burdens and profiles (Swarts et al 2012, Simbolo et al 2017. For example, somatic TP53 mutations and loss of 3p are common in NE carcinomas, yet rare in carcinoids (Rossi et al 2018). These molecular differences are directly related to differences in tobacco exposure, which is known to cause TP53 and other mutations (Gibbons et al 2014).…”
Section: Lung Neuroendocrine Tumorssupporting
confidence: 67%
“…Notably, one study that used NGS to investigate carcinoids did not provide the original sequencing data and, consequently, the sequencing results were not summarized in Table III; however, it was reported in the study that FGFR1 was highly expressed in carcinoids (39). In addition, Rossi et al (40) also reported that ERBB4 alteration was detected in carcinoids. Recently, Asiedu et al (41) used mRNA expression, single nucleotide polymorphism genotyping and a combination of exome and whole-genome sequencing to detect genomic alterations in 31 TC and 11 AC tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies of DIPNECH are needed to define the role of the NETest in the delineation of this ill-understood pathobiological condition. This lack of difference may reflect the current understanding of DIPNECH as a subset of peripheral carcinoid tumors with low malignant potential [26]. …”
Section: Discussionmentioning
confidence: 99%